A novel risk model for predicting potentially life-threatening arrhythmias in non-ischemic dilated cardiomyopathy (DCM-SVA risk). (15th September 2021) - Kayvanpour, Elham; Sammani, Arjan; Sedaghat-Hamedani, Farbod; Lehmann, David H.; Broezel, Alicia; Koelemenoglu, Jan; Chmielewski, Przemysław; Curjol, Angelique; Socie, Pierre; Miersch, Tobias; Haas, Jan; Gi, Weng-Tein; et al.
Abstract: Background: Non-ischemic dilated cardiomyopathy (DCM) can be complicated by sustained ventricular arrhythmias (SVA) and sudden cardiac death (SCD). By now, left-ventricular ejection fraction (LV-EF) is the main guideline criterion for primary prophylactic ICD implantation, potentially leading either to overtreatment or failed detection of patients at risk without severely impaired LV-EF. The aim of the European multi-center study DETECTIN-HF was to establish a clinical risk calculator for individualized risk stratification of DCM patients. Methods: 1393 patients (68% male, mean age 50.7 ± 14.3y) from four European countries were included. The outcome was occurrence of first potentially life-threatening ventricular arrhythmia. The model was developed using Cox proportional hazards, and internally validated using cross validation. The model included seven independent and easily accessible clinical parameters sex, history of non-sustained ventricular tachycardia, history of syncope, family history of cardiomyopathy, QRS duration, LV-EF, and history of atrial fibrillation. The model was also expanded to account for presence of LGE as the eight8h parameter for cases with available cMRI and scar information. Results: During a mean follow-up period of 57.0 months, 193 (13.8%) patients experienced an arrhythmic event. The calibration slope of the developed model was 00.97 (95% CI 0.90–1.03) and the C-index was 0.72 (95% CI 0.71–0.73). Compared to current guidelines, the model was able to protect the same number of patients (5-year risk ≥8.5%) with 15% fewer ICD implantations. Conclusions: This DCM-SVA risk model could improve decision making in primary prevention of SCD in non-ischemic DCM using easily accessible clinical information and will likely reduce overtreatment. Highlights: A seven-parameter model predicts life-threatening arrhythmia in dilated cardiomyopathy. MRI delivers additional information and increases model performance. This model performs well regardless of whether the patients carry CRT or not. Compared to LV-EF only, this model could significantly reduce ICD implantations.